Odpowiedzi

2010-03-11T12:20:41+01:00
Niestety poprzesuwać kolejne wyrażenia musisz sam.
a)
x^3 + x^2 + x + 1
---------------------
(x^4 - 1) : (x - 1)
-x^4 + x^3
---------------
= x^3 - 1
-x^3 + x^2
---------------
= x^2 - 1
-x^2 + x
------------
= x - 1
-x + 1
-----------
= =

(x^4 - 1) : (x - 1) = x^3 + x^2 + x + 1

b)
x - 5
--------------------------
(x^2-4x-3):(x+1)
-x^2 -x
-----------
= -5x - 3
5x + 5
-----------
= 2

c)
x^2 - 2
-----------------------
(x^4-4x^2+3):(x^2-2)
-x^4 + 2x^2
---------------
= -2x^2 + 3
2x^2 - 4
-----------------
= -1

d)
x^2 + 6
----------------------
(x^3+x^2+6x+6):(x+1)
-x^3 - x^2
----------------
= = 6x + 6
-6x - 6
-----------
= =